MEDIA KARTU SEBAGAI PENINGKATAN KEMAMPUAN BERBICARA BAHASA ARAB DI TKQ TAMRINUSSHIBYAN - Ratnasari, Tati; Bariah, Oyoh; Makbul, M. (Universitas Islam Negeri Sumatera Utara Medan, 2023)
Children who are slow in mastering the skills of reading Arabic letters and reciting them. Meanwhile, it is not appropriate for kindergarten teachers to emphasize reading, writing and arithmetic skills to their students. Indeed, it will later ease the work of elementary school teachers. However, what should be kept in mind by all parties is that the age of kindergarten children is the age of children to play, what needs to be taught to children is only gross motor skills, for example: balance as a provision for concentration or jumping. As a preschool institution, the main task of kindergarten is to prepare children by introducing various knowledge, attitudes or behaviors, skills and intellectuals and language so that they can adapt to actual learning activities in elementary schools in the future (Depdiknas, 2000: 2). This picture and letter card game or what the author calls Arabic numeral cards can provide a relaxed and informal learning situation, free from tension and anxiety. Children are actively involved and required to provide feedback and make a decision. Playing with picture cards should be fun and learning to read should be fun too.